KOBİ kredilerinde finansal analizin etkin kullanım koşulları - Keser, Esra (My University, 2008)
Günümüz küresel rekabet koşullarında, ülkelerin gelişme ve kalkınmalarında vazgeçilmez öneme sahip Küçük ve Orta Boy İşletmelerin önemi gün geçtikçe artmaktadır. Yıllar içerisinde, yaşanan ekonomik gelişmelerin de etkisiyle, sağladıkları üretim, istihdam ve yarattıkları katma değerle gerek gelişmiş, gerekse gelişmekte olan ülkelerin dikkatini çeken KOBİ’lerin önemi özellikle 1970’li yıllardan sonra büyük ölçüde artarak ülkelerin makro ekonomik politikalarının temelini oluşturmaya başlamışlardır. KOBİ’ler yarattıkları istihdam, üretim ve yaptıkları ihracatla ülke ekonomilerine sağladıkları faydaların yanı sıra esnek yapıları ve ölçeklerinin kendilerine sağladığı avantajla yeniliklere ve gelişmelere kolay uyum sağlayabilmekte ve tüketici taleplerine hızlı cevap verebilmektedirler. Sağladıkları sayısız yararın yanında yetersiz

kaynak yapılarıyla faaliyet gösteren KOBİ’lerin en önemli sorunlarının başında finansman sorunu gelmektedir. Finansman sorunlarının çözümünde, özellikle ülkemiz KOBİ’lerinin başvurdukları işletme dışı kaynakların başında banka kredileri gelmektedir. Fakat ülkemizdeki KOBİ’lere sağlanan banka kredilerinin oranına bakıldığında, bu oranın gelişmiş ülkelerle kıyaslandığında oldukça düşük olduğu görülmektedir. Bu durumun nedenlerini inceleyecek olursak bankalar açısından; bu tür işletmelerin küçük ve riskli oluşları ve ayrıca muhasebe ve kayıt sistemlerindeki eksiklikler sıralanabilir. İşletmeler açısından ise; bankalarca talep elden teminat vs. gibi koşulların ağırlığı ve faiz oranlarının yüksekliği söylenebilir. Öte yandan son yıllardaki gelişmelere bakıldığında, ülkemizdeki olumlu ekonomik gelişmelerin ve artan rekabet koşullarının neticesinde bankaların KOBİ’lere olan bakış açılarının değiştiği ve KOBİ’lere sağlanan kredi miktarında artış görüldüğü gözlemlenmektedir. Kredi hacminin artmasıyla beraber bankaların üstlendikleri olası risklerde artmakta, bunun neticesinde kredi risk ölçümü ve yönetimi de artan bir önem kazanmaktadır. Ülkemizde de uygulamaya başlanan Basel II standartlarının da risk odaklı fiyatlamaya ağırlık vermesi, konunun önemini arttırmaktadır. Kredilendirme aşamalarını incelediğimizde bu aşamaların, kredi başvurusuyla başlayıp kredi analizi, kredinin yapılandırılması ve kredi tahsisiyle süren ve kredinin izlenmesi ve sorunlu kredilerin yönetimi gibi aşamalarla devam eden detaylı bir süreç olduğu görülmektedir. Kredi başvurusu alındığında işletmenin geri ödeyebilme gücünü ölçmek açısından hayati öneme sahip işletme verilerinin finansal analizi, yalnızca kreditörlere değil, gerek işletme yönetimine gerekse işletmeyle ilgili taraflara önemli bilgiler sunmaktadır. İşletme faaliyet sonuçlarının değerlendirildiği ve işletmeyle ilgili gelecek tahminlerinin yapılmasında önemli veriler sağlayan finansal tablolar analizinin verimliliğini ve etkinliğini etkileyen çok çeşitli faktörler ve koşullar söz konusudur. Öncelikle işletme faaliyetleri sonucu oluşan mali tablo kalemlerinin işletme içi ve dışı pek çok faktörün etkisi altında oluştuğu unutulmamalıdır. Ayrıca mali tablolar analize hazırlanırken hesap kalemleri üzerinde gerekli arındırmaların yapılması ve özellikle enflasyonun mali tablolar üzerindeki etkisinin dikkate alınarak bu doğrultuda gerekli düzenlemelerin yapılması sağlıklı sonuçların alınmasını sağlayacaktır. Bütün bu unsurların yanı sıra, mali tablo analizini gerçekleştirecek mali analistin konusuna hakimiyeti, bilgi ve yetenekleri de mali tablo analizini etkileyecek önemli bir husustur. Öte yandan, KOBİ niteliğindeki işletmelerin verileri ve finansal bilgileri analiz edilirken büyük işletmelere kıyasla farklı bir bakış açısı ve yorumlama anlayışı gerekmektedir. Bilanço ve gelir tablosu değerleri büyüdükçe oranlamalar sonucu ortaya çıkan değerlerin yeterliliği incelenirken ayrı bir bakış açısı gerekir. Ayrıca işletme büyüklüğünün yanı sıra, işletmenin faaliyette bulunduğu sektörün yapısı ve sektör ortalama verileri de analizde göz önünde bulundurulması gereken unsurlardır. Etkin bir finansal analiz, sonuçların gerçekçi yorumu ve doğru tahminler kredilendirme aşamasında hayati önem taşımakta ve üstlenilen olası riskleri minimize etmektedir. ABSTRACT The importance of the small and the medium scale establishments (SMSE), which have indispensable importance for the development and the growth of the countries, increase day by day in the current global competitive conditions. The importance of the SMSE’s, which have attracted the attention of both the developing and the developed countries with their maintained production, recruitment and with their maintained value addition and also with the effects of the economical developments that had been seen within the years, have increased in great amounts especially after the 70’s and have created the basis for the macro economic policies of the countries. The SMSE’s harmonize easily with the innovations and the developments and respond rapidly to the requirements of the consumer with their flexible structures and with the advantages that their scale provide for themselves as well as the benefits, which they provide for the economy of the country with the deployment, the production and the export that they create. The foremost of the most important problems of the SMSE’s, which have their activities with inadequate resource structures as parallel with the numerous benefits that they provide, is the finance problem. The main way of dealing for the solution of the financial problems especially for the SMSE’s of our country as for the outside of their own establishment resources is to apply for the bank loans. But, when it is looked into the ratio of the loans that are issued to the SMSE’s of our country it can be seen that it is rather small when compared with the loans that are issued in the developed countries. If the reasons behind this situation is to be examined, then the facts that these kind of establishments are small and they carry risks from the point of view of the banks and in addition, the deficiencies in their accounting and the book keeping can be mentioned. For the point of view of the establishments, the burden of the conditions like the securities, etc that are demanded by the banks and the high rates of interest can be mentioned. One the other hand, when it is looked on the developments during the last years, it is observed that the standpoint of the banks against the SMSE’s have changed as the results of the positive economical developments in the country and as the result of the increased competitive conditions and it is observed that there is a increase on the amount of the loans that have been provided for the SMSE’s. The possible risks that the banks carry increase with the increase in the volume of the loans and as a result of this the loan risk measurement and the risk management becomes an important issue in increasing amounts. The fact that the Basel II standards, which has been started to be applied in our country, places its weight on the risk focused pricing increases the importance of the matter. When we study the phases of the loan products, we can see that these processes contain a detailed procedures as it starts with the loan application and continues with the loan analysis, structuring of the loan and with the issuing of the loan and continues still with the observation of the loan and the management of the problematic loans. The financial analysis of the data of the establishment, which has vital importance in relation to the measurement of the capability of the establishment to pay the loan back when the application for the loan is received, provide important information not only to the creditors but both to the management of the establishment and to the parties that have relations with the establishment. There are great deal of factors and conditions, which affect the productivity and the effectiveness of the analysis of the financial tables that provide important data for structuring the future estimations in relation to the establishment and where the results of the establishment activity results are being evaluated. It should be principally forgotten that the financial table items, which are created as the results of the establishment operations, are under the influence of great deal of internal and external factors. In addition, to carry out the required simplifications on the account items and to pay attention to the effect of the inflation on the financial tables and to carry out the required adjustments in this way shall provide the healthy results when the financial tables are being prepared for the analysis. In addition to all of these factors, the command, the knowledge and the capabilities of the financial analyst, who will carry out the analysis of the financial tables, are important issues that shall affect the analysis of the financial tables. On the other hand, it is necessary to have different point of view and the comprehension of comment when analyzing the data and the financial information of the establishments that are characterized as the SMSE as compared to the ones that are used for the large establishments. A different way of point of view becomes necessary when studying the capability of the amounts that are produced with the scaling up as the values of the balance sheet and the income table. In addition, the structure of the sector, where the establishment have its activities and the average sector data as well as the size of the establishment are the factors that should be paid attention to. An effective analysis, the realistic comment of the results and the right judgments all have vital importance for the loan issuing and minimizes the possible risks that have been undertaken.
Keywords: Bankalar ve Bankacılık; Finans; Kredilendirme_Bankalar ve Bankacılık; Küçük ve Orta Ölçekli İşletmeler (KOBİ)